PROCESS AUTOMATION IN THE CONTEXT OF INDUSTRY 4.0:: an analysis of the operations of an agricultural implements industry - Muniz, Eden; José Casagrande, Diego (Revista Interface Tecnológica, 2025)
This article aims to analyze how technological advances provided by Industry 4.0 - with an emphasis on automation - contribute to the optimization and efficiency of production operations. Industry 4.0 focuses on connectivity, that is, connecting an entire industry, from production to the sales system, is a reality of this new Industrial Revolution. The methodology used was Bibliographic Research and Case Study. This case study was developed in a company located in the city of Matão - São Paulo. The case study shows that the use of technological innovations, such as welding robots, provide improvements, agility and a greater degree of efficiency in manufacturing processes. When talking about Technological Innovation, the relationship with Industry 4.0 becomes clear because one is completely linked to the other.
Keywords: Technological Innovation; Industry 4.0